Design of Muskmelon Seed Peeling machine. Issue 1 (December 2020) - Imthiyas, A; Saravanan, M; Kumar, Praveen; Richard Meclar, F; Satyanarayan, D K
Abstract: A manually operated muskmelon seed peeling machine design was developed and evaluated in this study. The design was optimized to fabricate and to handle it easy. It consists of a hopper, the shelling chamber and an outlet unit. The developed muskmelon seed peeling machine is expected to shelling performance accounting for an optimal throughput capacity of about 93% and shelling damage rate of 7% at seed moisture content of 18.38%. By theoretical performance evaluation the machine can efficiently shell muskmelon seed. These muskmelon seed peeling machine technology can effectively take care of the challenges posed by erratic power supply and the high cost of gasoline. It providing support for small and medium scale farmers and food processor and at the same time make available quality melon seeds at low cost. The machine is semi-automatic in operation. Future scope for developing the machine is to make it to function fully automatic starting from automatic feeding up to self-hygienic packing.